Hubungan Qana'ah dengan Perilaku Konsumtif pada Mahasiswa Rantau - Anggara Fitrianta, Fisnu; Kutub Hardew, Ayatullah (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
Qana'ah is an important characteristic that overseas students must have in controlling consumer behavior. Overseas students with high Qana'ah traits will have low consumptive behavior. This research aims to determine the relationship between Qana'ah and consumer behavior among students from the Solo Raya area. The research method used is quantitative with a correlational approach. The number of samples in this research was 153 people based on a non-probability sampling technique, namely purposive sampling. The scale used consists of the qana'ah scale and consumer behavior. The analysis technique used is bivariate. The analysis results show the correlation value is -0.423** and sig. 0.000, then the hypothesis proposed by the researcher is accepted. This means that overseas students in Solo Raya have a negative relationship between qana'ah and consumer behavior. Keywords: Overseas Student; Consumptive Behavor; Qana’ah